Contested justice : the politics and practice of the International Criminal Court interventions - Vos, Christian M. de
"This timely, perceptive book brings together leading scholars and practitioners to reflect on the field of international criminal justice through focusing on a singular institution: the International Criminal Court (ICC). Drawing on a range of experience, empirical work, and normative theory, it seeks to come to grips with a remarkable development-the creation of a permanent, international court meant to adjudicate mass crimes-through assessing the ICC's work in practice, given now more than a decade of experience to explore"--